Epigenome-wide gene–age interaction study reveals reversed effects of MORN1 DNA methylation on survival between young and elderly oral squamous cell carcinoma patients - Xu, Ziang; Gu, Yan; Chen, Jiajin; Chen, Xinlei; Song, Yunjie; Fan, Juanjuan; Ji, Xinyu; Li, Yanyan; Zhang, Wei; Zhang, Ruyang (Frontiers in Oncology, 2022)
DNA methylation serves as a reversible and prognostic biomarker for oral squamous cell carcinoma (OSCC) patients. It is unclear whether the effect of DNA methylation on OSCC overall survival varies with age. As a result, we performed a two-phase gene–age interaction study of OSCC prognosis on an epigenome-wide scale using the Cox proportional hazards model. We identified one CpG probe, cg11676291MORN1, whose effect was significantly modified by age (HRdiscovery = 1.018, p = 4.07 × 10−07, FDR-q = 3.67 × 10−02; HRvalidation = 1.058, p = 8.09 × 10−03; HRcombined = 1.019, p = 7.36 × 10−10). Moreover, there was an antagonistic interaction between hypomethylation of cg11676291MORN1 and age (HRinteraction = 0.284; 95% CI, 0.135–0.597; p = 9.04 × 10−04). The prognosis of OSCC patients was well discriminated by the prognostic score incorporating cg11676291MORN1–age interaction (HRhigh vs. low = 3.66, 95% CI: 2.40–5.60, p = 1.93 × 10−09). By adding 24 significant gene–age interactions using a looser criterion, we significantly improved the area under the receiver operating characteristic curve (AUC) of the model at 3- and 5-year prognostic prediction (AUC3-year = 0.80, AUC5-year = 0.79, C-index = 0.75). Our study identified a significant interaction between cg11676291MORN1 and age on OSCC survival, providing a potential therapeutic target for OSCC patients.